2012
DOI: 10.1530/eje-11-0966
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided percutaneous microwave ablation of benign thyroid nodules: experimental and clinical studies

Abstract: Purpose: To obtain the treatment parameters of internally cooled microwave antenna and to evaluate the feasibility of ultrasound-guided percutaneous microwave ablation (MWA) for benign thyroid nodules. Materials and methods: MWAs were performed by microwave antenna (16G) in ex vivo porcine liver. The lesion diameters achieved in different groups (20, 25, and 30 W for 3, 5, 7, 10, and 12 min) were compared. The clinical study was approved by the ethics committee. Written informed consent was obtained from all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 124 publications
(135 citation statements)
references
References 31 publications
(67 reference statements)
5
125
1
2
Order By: Relevance
“…Nevertheless, only a few studies considering MWA efficacy in the treatment of benign solid thyroid nodules are available. In these studies, at the post-treatment follow-up (from 1 to 12 months), nodule volume reduction ranged from 45 to 65 % [76,77,81,82]. Feng et al reported an improvement of symptoms and cosmetic score [77].…”
Section: Clinical Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, only a few studies considering MWA efficacy in the treatment of benign solid thyroid nodules are available. In these studies, at the post-treatment follow-up (from 1 to 12 months), nodule volume reduction ranged from 45 to 65 % [76,77,81,82]. Feng et al reported an improvement of symptoms and cosmetic score [77].…”
Section: Clinical Resultsmentioning
confidence: 99%
“…In these studies, at the post-treatment follow-up (from 1 to 12 months), nodule volume reduction ranged from 45 to 65 % [76,77,81,82]. Feng et al reported an improvement of symptoms and cosmetic score [77]. In a recent study, 30 patients with a total of 34 benign thyroid nodules underwent MWA.…”
Section: Clinical Resultsmentioning
confidence: 99%
See 3 more Smart Citations